Novel Approach to Bile Duct Damage in Primary Biliary Cirrhosis: Participation of Cellular Senescence and Autophagy - Motoko Sasaki; Yasuni Nakanuma (International Journal of Hepatology)
Primary biliary cirrhosis (PBC) is characterized by antimitochondrial autoantibodies (AMAs) in patients' sera and histologically by chronic nonsuppurative destructive cholangitis in small bile ducts, eventually followed by extensive bile duct loss and biliary cirrhosis. The autoimmune-mediated pathogenesis of bile duct lesions, including the significance of AMAs, triggers of the autoimmune process, and so on remain unclear. We have reported that cellular senescence in biliary epithelial cells (BECs) may be involved in bile duct lesions and that autophagy may precede the process of biliary epithelial senescence in PBC. Interestingly, BECs in damaged bile ducts show characteristicsof cellular senescence and autophagy in PBC. A suspected causative factor of biliary epithelial senescence is oxidative stress. Furthermore, senescent BECs may modulate the microenvironment around bile ducts by expressing various chemokines and cytokines called senescence-associated secretory phenotypes and contribute to the pathogenesis in PBC.